2015
DOI: 10.1162/jocn_a_00762
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Macaque Middle STS Body Patch Neurons to Shape-preserving Stimulus Transformations

Abstract: Functional imaging studies in human and nonhuman primates have demonstrated regions in the brain that show category selectivity for faces or (headless) bodies. Recent fMRI-guided single unit studies of the macaque face category-selective regions have increased our understanding of the response properties of single neurons in these face patches. However, much less is known about the response properties of neurons in the fMRI-defined body category-selective regions ("body patches"). Recently, we reported that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 45 publications
5
29
0
Order By: Relevance
“…In agreement with our previous study (17) that showed similar responses and selectivity of midSTS body patch neurons for the original and silhouette versions of the objects, Bubbles revealed similar fragments for these two image versions. However, Bubbles revealed larger fragments and more frequently whole bodies for the silhouettes compared with the full images.…”
Section: Originalsupporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with our previous study (17) that showed similar responses and selectivity of midSTS body patch neurons for the original and silhouette versions of the objects, Bubbles revealed similar fragments for these two image versions. However, Bubbles revealed larger fragments and more frequently whole bodies for the silhouettes compared with the full images.…”
Section: Originalsupporting
confidence: 92%
“…We showed before that many midSTS body patch neurons respond to silhouettes of bodies (17). Silhouettes isolate shape contours, removing texture and shading information.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Another important unresolved question is the degree to which disparity contributes to well-studied inferotemporal representations such as those for faces [77] or body parts [87]. It has been shown that the face patches strongly overlap with regions activated by near (crossed) disparities [5], but the functional consequences of this overlap for face encoding by IT neurons have not yet been studied.…”
Section: Conclusion and Open Questionsmentioning
confidence: 99%